Teaching with digital badges best practices for libraries - Jacobson, Trudi E. 1957-; O'Brien, Kelsey 1986- (Lanham, Maryland Rowman & Littlefield, 2018)
"Teaching with Digital Badges: Best Practices for Libraries provides examples of how badges are enhancing and invigorating information literacy instruction. The editors share their experience implementing a metaliteracy badging system that has engaged more than 2,000 students across disciplines, secured faculty buy-in, and facilitated partnerships"--Provided by publisher.
Overview of micro-credentialing / Cinthya Ippoliti -- Forces of change for higher education : opening gates for digital badging / Trudi E. Jacobson -- Addressing stakeholder needs to establish meaningful digital badging in higher education / Laureen P. Cantwell and Kristyn K. Rose -- Digital badges in schools / Amanda Rose Fuller -- Badges can do that : ideas for using badges to enhance information literacy instruction / Allison Hosier -- Badging best practices / Kelsey L. O'Brien -- Pollak library spark tutorials / J. Lindsay O'Neill -- Competency-based education, badging, and the library / Michael Fosmire and Amy S. Van Epps -- Hot neoliberal commodities or tools for empowerment? : a badges case study and conversation / Emily Ford, Jost Lottes, Betty Izumi, and Dawn Richardson -- Badging and workplace information literacy : helping students prepare for the professional world / Megan Blauvelt Heuer -- Failing better : scaffolding learning with the metaliteracy badging system / Kelsey L. O'Brien.
Includes bibliographical references and index.
Keywords: Information literacy -- Study and teaching (Higher); Digital badges